Vertical Wind Speed Variation in a Metropolitan City in South China. Issue 4 (2nd April 2022) - Wu, Yueyuan; Li, Qinglan; Li, Guangxin; He, Bing; Dong, Lin; Lan, Haining; Zhang, Lijie; Chen, Shenpeng; Tang, Xiaoxin
Abstract: Severe wind with high altitudes may threaten the safety of the metropolitan city. This study investigates the relationship between the variation of vertical wind speeds (including 10 min average wind speed (avg‐wind) and 3 s average wind speed (gust wind)) and the height changes in Shenzhen, based on the hourly wind speeds observed on the Shenzhen Meteorological Gradient Tower, Ping An Building, and in the Central Park. The samples are grouped according to the wind speeds. The power law and least square fitting methods are used to obtain the Hellman coefficient value for each group. We find that the fitted Hellman coefficients for both gust wind and avg‐wind are subject to the exponential decay function. When the winds reach their corresponding high percentile level, that is, around 80% of the wind record, the Hellman coefficients almost keep constant. The Hellman coefficient is generally higher over the urban area than that over the rural area. Over the urban area, the Hellman coefficient is with the range of 0.49 ∼ 0.169 for gust wind and 0.64 ∼ 0.327 for the avg‐wind; while over the rural area, the Hellman coefficient is with the range of 0.33 ∼ 0.077 for gust wind and 0.49 ∼ 0.153 for the avg‐wind. There is an apparent diurnal variation of the Hellman coefficient, which is lower during the daytime and higher during nighttime. The monthly variation of the Hellman coefficient over the urban area is not evident, mainly due to the city's climate condition and urban heat island. Plain Language Summary: The value of the Hellman coefficient usually decreases with the increase of the wind speed. The fitted Hellman coefficients for both gust wind and avg‐wind are subject to the exponential decay function. When the winds reach their corresponding high percentile level, that is, around 80% of the wind record, the Hellman coefficients almost keep constant. Key Points: The Hellman coefficient decreases with increased wind speed for a certain topography area, subject to the exponential decay function When the wind reaches its high percentile level for a certain topography area, the Hellman coefficients almost keep constant The monthly variation of the Hellman coefficient is not apparent over the urban area in Shenzhen due to the urban heat island and its climate